Geometry design of tethered small-molecule acceptor enables highly stable and efficient polymer solar cells - Yang Bai; Ze Zhang; Qiuju Zhou; Hua Geng; Qi Chen; Seoyoung Kim; Rui Zhang; Cen Zhang; Bowen Chang; Shangyu Li; Hongyuan Fu; Lingwei Xue; et al. (Nature Communications, 2023)
Abstract With the power conversion efficiency of binary polymer solar cells dramatically improved, the thermal stability of the small-molecule acceptors raised the main concerns on the device operating stability. Here, to address this issue, thiophene-dicarboxylate spacer tethered small-molecule acceptors are designed, and their molecular geometries are further regulated via the thiophene-core isomerism engineering, affording dimeric TDY-α with a 2, 5-substitution and TDY-β with 3, 4-substitution on the core. It shows that TDY-α processes a higher glass transition temperature, better crystallinity relative to its individual small-molecule acceptor segment and isomeric counterpart of TDY-β, and a more stable morphology with the polymer donor. As a result, the TDY-α based device delivers a higher device efficiency of 18.1%, and most important, achieves an extrapolated lifetime of about 35000 hours that retaining 80% of their initial efficiency. Our result suggests that with proper geometry design, the tethered small-molecule acceptors can achieve both high device efficiency and operating stability.